"A Second-Chance at Being a Parent": Grandparent Caregivers' Reported Communication and Parenting Practices with Co-Residential Grandchildren. Issue 3 (3rd July 2019) - Freeman, Jessica D.; Elton, Jessica; Lambert South, Andrea
ABSTRACT: Grandfamilies, family structures in which grandparent(s) co-reside with and assume a primary caregiving role for at least one grandchild, are increasingly common in the United States. This qualitative, exploratory study, informed by family communication patterns theory (FCPT), illuminated the reported communication beliefs and practices of grandparents who serve as primary caregiver to at least one grandchild. Hybrid thematic analysis, combining FCTP with inductive analysis, was used to analyze 21 semi-structured interviews with grandparents. Results yielded four themes describing grandparents' reported communicative practices: creating opportunities for listening and dialogue, talking about emotion, emphasizing openness, and allowing questioning ; and three themes describing the impact of second-chance parenting: increased resources, acquired wisdom, and matured emotionally . Implications for grandfamily communication research in light of hybrid analyses and FCPT are discussed.